Vegan cupcakes take over the world : 75 dairy-free recipes for cupcakes that rule - Moskowitz, Isa Chandra (Marlowe, 2006)
The authors offer delicious, cheap, dairy-free, egg-free and vegan-friendly recipes like Classic Vanilla Cupcakes (with chocolate frosting), Crimson Velveteen Cupcakes (red velvet with creamy white frosting), Linzer Torte Cupcakes (hazelnut with raspberry and chocolate ganache), Chai Latte Cupcakes (with powdered sugar) and Banana Split Cupcakes (banana-chocolate chip-pineapple with fluffy frosting). Included also are gluten-free recipes, decorating tips, baking guidelines, vegan shopping advice, and Isa's true cupcake anecdotes from the trenches.--From publisher description.